A Randomized Comparison of two Short Intensive Chemotherapy Regimens in Children and Young Adults With Osteosarcoma: Results in Patients With Metastases: A Study of the European Osteosarcoma Intergroup. (1997) - Bramwell, Vivien H. C.; Burgers, Marion V.; Souhami, Robert L.; Taminiau, Antonie H. M.; Van Der Eijken, Jan W.; Craft, Alan W.; Malcolm, Archie J.; Uscinska, Barbara; Kirkpatrick, Anna L.; Machin, David; Van Glabbeke, Martine M.
Abstract : Purpose . To report the outcome of 37 patients with metastatic osteosarcoma entered into a large randomized trial (EOI 80831/MRC B002) comparing two different regimens of chemotherapy in patients with osteosarcoma. Methods . Patients with biopsy-proven osteosarcoma localized and metastatic, age 40 years or younger, were randomized to receive either two-drug treatment with doxorubicin/cisplatin (DOX 25 mg m − 2 day − 1 × 3 + DDP 100 mg m − 2 on day 1 q 3 weeks × 6 courses) or three-drug treatment comprising high-dose methotrexate (HDMTX 8 mg m − 2 administered every4 1 2 weeks × 4 courses) given 10 days before DOX/DDP. Results . Twenty-four patients with metastatic disease received the two-drug arm treatment and 13 received three-drug treatment. Despite chance imbalance in numbers, there were no major differences in age, sex, primary site or performance status. Baseline alkaline phosphatase (AP) was elevated more frequently (96 vs 42%) in the two-drug arm. Twenty-one of 24 patients in the two-drug arm and 11/13 patients in the three-drug arm had evaluable primary tumors concurrent with metastases. Respective clinical response rates for the two- and three-drug arms were 48% and 40% for primary tumors, and 33% and 55% for metastases. Respective survivals at 2 and 4 years were 36% and 9% for the two-drug arm, and 69% and 52% for the three-drug arm, and survival was better for patients with normal AP at presentation. When adjusted for AP, survival was not significantly different between the two treatments (hazard ratio 0.52, 95% confidence interval 0.22–1.23, p = 0.14). There were three long-term survivors among the metastatic patients, all of whom received the three-drug therapy. Discussion . It is likely that random bias in the population (small numbers, imbalance in size of groups, uneven distribution of AP) accounts for the difference in outcome favoring the three-drug treatment in patients with metastatic disease. More reliance can be placed on the finding that disease-free and overall survival in the adjuvant component of this study (Bramwell et al., J Clin Oncol 1992; 10: 1579–91) were better after two-drug treatment.